Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1007/s10681-012-0856-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of three cycles of full-sib reciprocal recurrent selection in two maize populations from the Northeast of Spain

Abstract: In Europe a heterotic pattern commonly used in maize breeding is "American Dent× European Flint". Maize breeding programs generally use only a small portion of the useful genetic variability present in the local open-pollinated varieties which, otherwise, have a poor performance that hampers their use. Two maize composites, EZS33 formed by open-pollinated flint varieties from dry or Mediterranean Spain, and EZS34 from USA dent populations, were developed in Zaragoza (Spain). Both were subjected to three cycles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 25 publications
4
8
1
Order By: Relevance
“…The response in the varietal crosses for grain yield and other agronomic traits was greater than the response of the various selection cycles of the two composites, suggesting that dominance was the major type of gene action involved (Keeratinijakal and Lamkey 1993;Souza Jr and Pinto 2000). Inconsistent trends in grain yield observed in varietal crosses in the present study was consistent with the results reported in other studies (Romay et al 2011;Peña-Asin et al 2013). The linear response obtained for grain yield in our program was similar to the response obtained in other RRS programs (Coors 1999;Peña-Asin et al 2013).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The response in the varietal crosses for grain yield and other agronomic traits was greater than the response of the various selection cycles of the two composites, suggesting that dominance was the major type of gene action involved (Keeratinijakal and Lamkey 1993;Souza Jr and Pinto 2000). Inconsistent trends in grain yield observed in varietal crosses in the present study was consistent with the results reported in other studies (Romay et al 2011;Peña-Asin et al 2013). The linear response obtained for grain yield in our program was similar to the response obtained in other RRS programs (Coors 1999;Peña-Asin et al 2013).…”
Section: Discussionsupporting
confidence: 93%
“…Responses to selection in the various selection cycles of the two composites in the present study were inconsistent for most traits while others remained unchanged until C 4 , which agrees with the reports of Souza Jr (1999) and Romay et al (2011). Grain yield improved in TZL COMP4 at a rate of 0.9% per cycle, although the largest mean performance was reached during the third selection cycle, whereas, the improvement for grain yield was not consistent in TZL COMP3 resulting in a negative response, consistent with the negative, positive or lack of response observed in one or two populations improved through RRS in other breeding programs (Butruille et al 2004;Moreno-Perez et al 2004;Peña-Asin et al 2013;Reis et al 2013). A plausible explanation for negative response of TZL COMP3 could be because it was formed by crossing an orange maize variety from Thailand (Suwan 1-SR) with an adapted variety (TZB-SR) developed at IITA (Menkir et al 2015).…”
Section: Discussionmentioning
confidence: 54%
“…Kling, 1999;Rademacher et al, 1999;Souza and Pinto, 2000;Santos et al, 2005). However, the realized genetic gain in grain yield in our study was higher than the genetic gains reported in other studies varying from 2.1 to 3.0% (Paterniani and Vencovsky, 1978;Hallauer, 1984;Peña-Asin et al, 2013). The difference between our results and other RRS programs could be attributable to differences in the test environments, the genetic base of the populations studied, the number of progenies selected for recombination in each cycle, and selection intensity.…”
Section: Discussioncontrasting
confidence: 57%
“…In addition, the improved population crosses could be used as elite openpollinated cultivars until conventional hybrids involving inbred lines are developed. Peña-Asin et al (2013) reported a 3.0% cycle −1 increase in grain yield after three cycles of full-sib RRS in two maize composites. Hallauer (1992) stated that genetic gain might not always be apparent from cycle to cycle and, in some instances, it could even be erratic among cycles.…”
Section: Genetic Advance In Grain Yield and Other Traits In Two Tropimentioning
confidence: 99%
See 1 more Smart Citation